Tip-induced band bending on Sr/Si(100)-2×3 reconstructed surface - Du, Wenhan (2018)
Using Vary-temperature Scanning Tunnelling Microscopy (VT-STM), the geometric and electronic structures of technological important Sr/Si(100)-2×3 surface were investigated. Two important findings explained in this research. First, a phenomenon similar to quantum corral observed in the empty state STM image that near the bottom of the conduction band. This is aroused from the surface vacancies and phase boundary in the Sr/Si(100)-2×3 surface. And a new Sr/Si(100)-2×6 reconstructed structure coexist with Sr/Si(100)-2×3 surface has been prepared by accurately controlling the annealing temperature, both surface’s geometric structures can be described by dimer vacancy model. Second, tip-induced band bending phenomenon was observed in the Sr/Si(100)-2×3 surface at substrate temperature range from 76K to 300K. Experimental LDOS results from n and p-type silicon substrate confirms 0.3eV up the motion of the valence band minimum compare with bare Si(100)-2×1 surface. Buckled and unbuckled silicon dimer coexisting in the Sr/Si(100)-2×3 reconstructed surface contribute to the tip-induced band bending and energy band gap widen phenomenon. Which confirms that Sr atoms transfer electrons to the nearby silicon dimers, make the first layer silicon dimers kept at unbuckled state.